Failure analysis for a dry-pulverized coal gasifier burner made up of Inconel 718 superalloy. (March 2019) - Lu, Jintao; Yang, Zhen; Zhou, Yongli; Huang, Jinyang; Yan, Jingbo; Dang, Yinying; Yuan, Yong; Gu, Yuefeng
Abstract: Early failure of the coal gasifier burner used in integrated gasification combined cycle plants poses serious technical and safety issues. The aim of this study was to determine the causes of a failed burner based on chemical composition of material and characteristics of corrosion products and cracks. Furthermore, microstructures of the failed component at different depths were compared to investigate the phase degradation. The study found that sulfurization and chlorination were the main causes for the failure of current coal gasifier burner. Sulfidation contributed to the crack propagation, while chlorine concentrated in the corrosion layer produced significant cracks and spallations. The overheating was supposed to be responsible for the non-uniform distribution of precipitations in the failed burner from fire side to water side. Highlights: Sulfidation contributed to crack propagation in the substrate alloy Inconel 718. Chlorine concentrated in the corrosion layer led to cracks and spallations in both the slag layer and the reaction layer. Overheating led to the non-uniform distribution of precipitations from the gasification side to the water-cooling side.